1996
DOI: 10.1016/s0022-5347(01)66252-9
|View full text |Cite
|
Sign up to set email alerts
|

Differential Diagnosis of Prostatism: a 12-year Retrospective Analysis of Symptoms, Urodynamics and Satisfaction with Therapy

Abstract: Symptomatic men with prostatism are presenting with a greater prevalence of significant nocturia and daytime frequency than in the past with no change in urodynamic findings. In addition, patient level of satisfaction remains greater with surgical than medical therapy regardless of the urodynamic presence of bladder outlet obstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 12 publications
1
26
0
2
Order By: Relevance
“…Kaplan et al found that among a subset of 121 patients treated surgically, only 51% had urodynamic evidence of bladder outlet obstruction. 25 However, the degree of patient satisfaction and symptomatic improvement did not correlate with the urodynamic findings. Jensen et al prospectively studied 62 men selected for prostatectomy by physicians who were blinded to the preoperative urodynamic findings.…”
Section: Discussionmentioning
confidence: 93%
“…Kaplan et al found that among a subset of 121 patients treated surgically, only 51% had urodynamic evidence of bladder outlet obstruction. 25 However, the degree of patient satisfaction and symptomatic improvement did not correlate with the urodynamic findings. Jensen et al prospectively studied 62 men selected for prostatectomy by physicians who were blinded to the preoperative urodynamic findings.…”
Section: Discussionmentioning
confidence: 93%
“…However, a substantial number of these patients have disappointing results and coupled with reluctance to avoid surgery. These patients eventually present as CUR at a later stage thus a advanced age group presentation with CUR is observed [13,[16][17][18][19][20][21][22][23][24][25][26][27]. …”
Section: Discussionmentioning
confidence: 99%
“…This is in agreement with the observations made by Davies JA [17] in their review that the common symptoms of which the patients are aware of are frequency, decrease flow and hesitancy. A retrospective study by SA Kaplan et al [19] concluded that most common symptom of BOO was nocturia followed by increase frequency of urine, decrease flow of urine, hesitancy, dribbling, straining, sensation of incomplete voiding and incontinence.…”
Section: Neurological Diseasementioning
confidence: 99%
“…Yaklaşık %15-30 hastada obstrüksiyonun cerrahi tedavisine rağmen işeme disfonksiyonunun ve de özel-likle depolama semptomlarının devam ettiği gösterilmiştir [12,13]. Çıkım obstrüksiyonuna mesanenin cevabı süreye, obstrüksiyonun boyutuna ve natürüne bağlı olarak değişiklikler göstermekte olup MÇO ile mesane dekompansasyonu arasındaki direk ilişki henüz kanıtlan-mamıştır [14]. Ancak PAE tedavisinde mesane dekompansasyonunun varlığı hasta seçiminde göz önünde bulundurulmalıdır.…”
Section: Bph Ve Klinik Kavramlarunclassified